Salmon fishing in the yemen eaudiobook - Torday, Paul (Recorded Books Inc., 2012)
Author Paul Torday makes his debut with this clever absurdist novel. Fisheries scientist Dr. Alfred Jones is approached by an extravagantly wealthy sheik with a novel plan. To foster goodwill, the sheik would like to introduce salmon fishing to Yemen-the same Yemen that is largely a desert-and politicians think it's a great idea. "A remarkably assured first novel, this one is a pure delight."-Booklist, starred review